THERMAL ANALYSIS OF THE MODIFIED MAGNESIUM-CONTAINING SILUMINS WITH DIFFERENT TYPE OF MODIFIER - I. V. Rafalskij; G. V. Dovnar; S. V. Kiselev; P. E. Lushchik; A. V. Belskij (Литьë и металлургия)
The modification of the eutectic structure in aluminum-silicon-magnesium alloys related to the thermal parameters analysis is investigated. The magnitude of the eutectic undercooling and eutectic arrest depression caused by modifying sodium and strontium has been correlated to the eutectic microstructure accordingly to the type of modifier. The reason for difference of cooling curves and microstructure of aluminum-silicon-magnesium alloys modified sodium and strontium is changing in growth mode of eutectic crystals from the liquid.